Array based real-time measurement of fluid viscosities and mass-densities to monitor biological filament formation. Issue 7 (11th March 2019) - Oliva, Paolo; Bircher, Benjamin Andreas; Schoenenberger, Cora-Ann; Braun, Thomas
Abstract : A membrane-based resonator detecting filament formation of biological samples in a label- and functionalization-free manner. Abstract : Liquid mass density and viscosity are fundamental characteristics of fluids. Their quantification by means of classical viscosity and density meters has several drawbacks: (i) the liquid-density and the viscosity cannot be measured simultaneously, (ii) sample volumes in the mL-range are consumed, (iii) the measurements cannot be multiplexed, and, (iv) the quantifications are time-consuming (minutes). Nano-mechanical transducers promise to overcome these limitations. We use fully clamped, gold coated silicon-nitride membranes with a thickness of 200 nm to measure liquid viscosity and density of samples of 1 μL volumes residing above the membrane in a miniature well. Photo-thermal actuation is used to excite the membrane, and an optical deflection system measures the response. From the response spectra, the eigenfrequency ( f ) and the quality ( Q ) factor are extracted and used to determine liquid density and viscosity by applying a three-point calibrated, simplified lumped model. We tested the system using calibrated solutions with viscosities in the range of 1–219 mPa s and mass densities between 998 kg m −3 and 1235 kg m −3 . Real-time measurements were performed that characterize the polymerization of G-actin to F-actin filaments. The method presented promises to overcome the aforementioned limitations and thereby enables the real-time characterization of sub-μL sample volumes in a multiplexed manner.